Financial Management and Digital Marketing Training for MSMEs in Fostered Villages Post Pandemic - Aprilda Yanti; Zahara meutia; Putri Mauliza; Richna Handriyani; Debi Masri (Outline Publisher, 2025)
The COVID-19 pandemic has had a significant impact on the sustainability of micro, small, and medium enterprises (MSMEs), especially in rural areas. Weak financial management and minimal use of digital technology are two main obstacles that exacerbate the condition of MSMEs in facing the crisis. This community service activity aims to increase the capacity of MSME actors in fostered villages through applicable and sustainable financial management and digital marketing training. The training method is carried out in a participatory and practical manner, involving 25 MSME actors from various sectors. The evaluation was carried out using a quantitative and qualitative approach to measure changes in participants' understanding and skills before and after training. The results showed a significant increase in aspects of understanding financial management (from 35% to 85%), financial recording skills (from 25% to 80%), understanding digital marketing (from 30% to 90%), and skills in using social media for business promotion (from 20% to 88%). In addition, participants showed increased confidence in managing their businesses more professionally and based on data. These findings indicate that integrated training that combines financial and digital aspects can strengthen the resilience and competitiveness of MSMEs post-pandemic. The recommendation from this activity is the importance of continued mentoring and ongoing support from the village government and educational institutions to maintain the sustainability of the training impact.